2017
DOI: 10.1155/2017/3849152
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis Comparing Postoperative Complications and Outcomes of Femtosecond Laser-Assisted Cataract Surgery versus Conventional Phacoemulsification for Cataract

Abstract: Objective. This meta-analysis aimed to compare the outcomes and postoperative complications between femtosecond laser-assisted cataract surgery (FLACS) and conventional phacoemulsification cataract surgery (CPCS). Methods. Bibliographic databases, including PubMed, Embase, and Cochrane library, were systematically searched for references on or before September 2015 regarding the outcomes and complications by FLACS or CPCS. Data on corneal endothelial cell loss, uncorrected distance visual acuity (UDVA), correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
0
39
0
1
Order By: Relevance
“…Illness uncertainty is always identified in chronic diseases due to such factors as long course of disease, lack of accurate information, complexity of the treatments, and loss of somatic functions and so on, so as glaucoma and cataract in our study 13 , 14 . We identified significantly higher illness uncertainty in glaucoma patients compared with cataract patients, probably because glaucoma tends to be associated with a younger onset age, more pain, more complications and more complex treatments, including both medications and surgeries 15 , 16 . The univariate logistic results showed us that illness uncertainty was positively associated with HADS score in both glaucoma patients and cataract patients.…”
Section: Discussionmentioning
confidence: 90%
“…Illness uncertainty is always identified in chronic diseases due to such factors as long course of disease, lack of accurate information, complexity of the treatments, and loss of somatic functions and so on, so as glaucoma and cataract in our study 13 , 14 . We identified significantly higher illness uncertainty in glaucoma patients compared with cataract patients, probably because glaucoma tends to be associated with a younger onset age, more pain, more complications and more complex treatments, including both medications and surgeries 15 , 16 . The univariate logistic results showed us that illness uncertainty was positively associated with HADS score in both glaucoma patients and cataract patients.…”
Section: Discussionmentioning
confidence: 90%
“… 11 , 12 , 13 The 2016 Cochrane Review of FLACS versus PCS concluded there was limited evidence to determine equivalence or superiority and that large adequately powered RCTs were needed. 11 Three meta-analyses have been published, 12 , 13 , 14 one finding superior refractive outcomes for FLACS, and the others finding no statistically significant differences in terms of patient-reported visual and refractive complications. Two large RCTs have recently been published: the French FEMCAT (Femtosecond Laser Assisted Cataract Surgery) trial, 15 and a UK trial of 400 eyes that found similar visual outcomes between arms and a statistically significantly lower posterior capsule tear rate in the laser arm.…”
mentioning
confidence: 99%
“…[21] The evidence shows that capsulotomy performed with FLACS shows better shape and size consistency than capsulotomy performed using conventional techniques. [22][23][24][25] A well-shaped and centered circular 5 mm capsulorhexis is, in our experience, easier to achieve using the femtosecond laser. In cases where the OCT software cannot precisely identify the anterior capsule due to the lack of normal pattern recognition (e.g., lenticonus), its position can be easily defined manually using intraoperative real-time OCT.…”
Section: Discussionmentioning
confidence: 56%